Interfacial structure-property relationship in a carbon nanotube-reinforced aluminum alloy matrix composite fabricated by an advanced method - Nateq, Behzad; Haddad-Sabzevar, Mohsen; Sajjadi, Seyyed Abdolkarim; Pellizzari, Massimo (Materials characterization, 2023)
In our previous study, a bulk carbon nanotube (CNT)-reinforced aluminum alloy matrix composite with enhanced comprehensive mechanical properties was fabricated via an advanced powder processing, denoted as Mixed Ball-Milling (MBM) technique. Here, we attempted to explore the relationship between the composite microstructure and the elevated mechanical behavior with a special focus on CNT/Al interfacial features. To this end, high-resolution scanning transmission electron microscopy (HRSTEM) imaging combined with Raman spectroscopy were conducted to take a panoramic view of the subject. It was shown that in addition to the matrix heterogeneous grain structure and maintaining the structural integrity of CNTs, the interfacial bonding structure can be tailored using MBM methodology. Indeed, the formation of aluminum oxide nanophases in and around acid treatment-induced oxygen defects not only contributed to CNT structural conservation but also facilitated the load-transfer capability of the composite. A semi-quantitative analysis, performed on Raman spectroscopy data, authenticated that the aluminum carbide (Al4C3) formation was significantly restricted in the MBM processing, probably due to the presence of oxide species. The findings may also grant insight into the seldom-studied role of surficial oxygen defects in carbon-containing metal matrix composites. •The CNT/Al alloy composite showed a satisfactory combination of strength and ductility.•The relationship between the enhanced mechanical properties and composite microstructure was investigated.•Three determinative microstructural features were proposed among which CNT/Al interface quality was elaborately explored.•The possible role of acid treatment-induced oxygen defects in facilitating the nanophase formation was postulated.